CHOOSING THE TEST AUTOMATION SYSTEM ACCORDING TO CUSTOMER REQUIREMENTS - Andrei Popov; Myroslav Momot; Alina Yelizieva (Сучасний стан наукових досліджень та технологій в промисловості, 2022)
The subject of the research are methods and technologies for automating the process of software product testing. The aim of the work is to optimize the time and costs for performing automated testing of software products. The following tasks were solved: analysis of existing software testing automation systems; formation of system of selection criteria for testing automation systems; development of formalized model of selection process; development of automation system selection algorithm considering customer's requirements; development of UML diagrams for presentation of functional capabilities of developed application; development of application for informational support of selection process. To solve these tasks, we used methods of system analysis, theory of sets and technologies of cross-platform applications development. The following results were obtained: The most popular systems of test automation have been analyzed, their scope and main capabilities have been singled out. Selection criteria are singled out, divided into qualitative and quantitative. Formalized model for choosing test automation systems taking into account their characteristics and customer requirements is proposed. Developed UML diagram shows the functionality of the developed subsystem. The proposed algorithm for determining the re-recommended system of test automation allows us to take into account the vectors of criteria for testing systems. On the basis of the formalized model and algorithm we developed a subsystem that allows us to determine the optimal variant of test automation system on the basis of the introduced selection criteria. Conclusions: informational support for choosing a test automation system for software products based on the developed algorithm takes into account the customer's requirements and the characteristics of the existing systems, which allows us to select the most preferable option out of the possible systems. The main result of the developed subsystem is a recommendation for a user to use an automated testing system, taking into account customer requirements.